Fuzzy Rules for Secure Off-Grid System - Gabriel Cibira; Zdislav Exnar; Marcela Koscova (Advances in Electrical and Electronic Engineering, 2014)
Stand-alone off-grid power supply system is a necessity for applications when electrical power distribution network is inaccessible. Internal and external subject security aspects should be valued, and the system should be optimized to obtain properly working, never-failing and secure local electrical power supply system. Internal security aspects result from both security concept and used technologies. Internal threats contain fire ignition, flooding, electrical cables melting and other threats arising from intrinsic materials or subsystems characteristics, at standard conditions of use. Additional external aspects include anti-theft protection, breaking doors or windows signaling and countermeasure, weather extremes alert, etc. Both internal and external aspects necessarily induce additional off-grid power system or subject monitoring that might be performed by supervising security subsystem. This paper provides a solution for off-grid security subsystem. It consists from pervasive sensor circuits, fuzzy controlled diagnostics and executive actuators. Cooperated fuzzy logic diagnostic and control device enables to evaluate anticipated threats and dynamically generates the most appropriate decisions about real threat existence that leads to improvement of system protection. Proposed fuzzy rules are particularly discussed in the paper.